2016
DOI: 10.1016/j.radmeas.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Natural and laboratory TT-OSL dose response curves: Testing the lifetime of the TT-OSL signal in nature

Abstract: This study compares natural and laboratory generated thermally transferred optically stimulated luminescence (TT-OSL) dose response curves (DRCs) for fine-grain quartz extracts from the Luochuan loess section in central China. Both DRCs saturate at high doses relative to the quartz OSL signal; the natural TT-OSL DRC saturates at about 2200 Gy and laboratory DRCs saturate at about 2700 Gy. However, the natural and laboratory TT-OSL DRCs deviate from one another at circa 150 Gy resulting in TT-OSL equivalent dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Several modifications of the protocol have been tested on 20-41 µm quartz grains from a single sample by Hernandez et al (2012); they concluded that only samples that did not show significant changes between the first and subsequent cycles and/or did not need high temperature treatment at the end of each cycle were suitable for TT-OSL dating. Chapot et al (2016) applied a slightly different TT-OSL protocol to 4-11 µm quartz grains from a sedimentary sequence with an independent time scale reaching back 1 million years.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Several modifications of the protocol have been tested on 20-41 µm quartz grains from a single sample by Hernandez et al (2012); they concluded that only samples that did not show significant changes between the first and subsequent cycles and/or did not need high temperature treatment at the end of each cycle were suitable for TT-OSL dating. Chapot et al (2016) applied a slightly different TT-OSL protocol to 4-11 µm quartz grains from a sedimentary sequence with an independent time scale reaching back 1 million years.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…A similar approach had been applied to the testing of OSL signals (Chapot et al, 2012). Chapot et al (2016) concluded that the source trap for the TT-OSL had insufficient thermal stability for dating beyond 50 ka, having a lifetime at 10°C of ~174 ka. However, in a study of single sand-sized grains of quartz from Atapuerca, Spain, Arnold et al (2015) used a similar protocol to that of Chapot et al (2016) and obtained ages between ~240 and ~930 ka that were in agreement with the independent chronology.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…One explanation could be that they reach natural saturation at the same dose. To explore this option, we examined the natural saturations of these three signals at the Luochuan loess section in China, where natural DRCs were constructed (Chapot et al, 2016;Ankjaergaard et al, 2016;Li et al, 2018). There, natural DRCs suggest field saturation at about 2000 Gy for both TT-OSL and VSL.…”
Section: Natural Saturation Profilesmentioning
confidence: 99%
“…Nevertheless, a more comprehensive investigation revealed different limitations of using these signals. For example, the TT-OSL signal is thermally unstable, producing therefore only minimum ages after a few hundred thousand years (Adamiec et al, 2010;Shen et al, 2011;Chapot et al, 2016;Faershtein et al, 2018); it appears that the natural growth of the VSL signal cannot be properly described with the single aliquot regenerative (SAR; Murray and Wintle, 2000) constructed dose response curve (DRC) generally used for De determination (Ankjaergaard et al, 2016;Ankjaergaard, 2019). There is evidence of age overestimation for the pIRIR 290 and athermal signal loss (termed anomalous fading) issues for the pIRIR signals measured at lower temperatures (Lowick et al, 2012;Tsukamoto et al, 2017).…”
mentioning
confidence: 99%
“…One explanation could be that they reach natural saturation at the same dose. To explore this option, we examine the natural saturations of these three signals at the Luochuan loess section in China, where natural DRCs were constructed (Chapot et al, 2016;Ankjaergaard et al, 2016, Li et al, 2018. There, natural DRCs suggest field saturation at about 2000 Gy for both TT-OSL and VSL.…”
Section: Natural Saturation Profilesmentioning
confidence: 99%